Terreiros and Quilombos in Brazil, a praise for resistances - Creston, Helena Tuler (2020)
This article problematizes the patrimonial field through the rhizomatic way of thinking.  The general objective is to question the policies anchored in the identity issue and the territorial law policies in Brazil. For that, we put ourselves in a position against the dominant power/knowledge and make a praise for resistances... for stocks that survive. They’re study objetcs which bring events that caused ruptures and connections. They have specific timeframes in their emergencies, but they’re important survivals to be highlighted ”“ survivals of territorial hegemonic processes guided by the capital. Survivals that use the identity concept to guarantee their rights. The two studies presented Terreiro Casa Branca (Salvador/BA) and Quilombo Caçandoca (Ubatuba/SP) highlight the terreiros and quilombos as “Black Territories”, the spatially black resistance.